Chemopreventive Effects of Silibinin on Colitis-Associated Tumorigenesis by Inhibiting IL-6/STAT3 Signaling Pathway - Zheng, Rongjuan; Ma, Jiaheng; Wang, Dan; Dong, Wenxiao; Wang, Sinan; Liu, Tianyu; Xie, Runxiang; Liu, Li; Wang, Bangmao; Cao, Hailong (Mediators of Inflammation, 2018)
Inflammatory bowel disease (IBD), characterized by sustained inflammation, is a latent risk factor of colon tumorigenesis. Silibinin has been reported to be anti-inflammatory and antineoplastic, but its efficacy on colitis-associated cancer (CAC) has not been reported. Interlukin-6/signal transducer and activator of transcription 3 (IL-6/STAT3) is the key signaling pathway involved in CAC. We evaluated the chemopreventive effect of silibinin on a CAC mouse model and determined its impact on IL-6/STAT3 signaling. Intestinal tumor cells (IMCE and HCT-116 cell lines) were also treated by graded concentration of silibinin, and cellular viability was determined. Silibinin (750 mg/kg/day) was administered to an azoxymethane/dextran sulfate sodium (AOM/DSS) C57BL/6 mouse model for 10 weeks by gavage. Body weight, colon length, and the amount and diameter of colon tumors were documented, respectively. Specimens were subjected to H&E staining for colitis and tumor scoring, immunohistochemical staining and terminal deoxynucleotidyl transferase dUTP nick end labeling for proliferation assessment, and immunofluorescent staining for intestinal mucosa barrier assessment. Production of inflammatory cytokines was determined by real-time PCR. IL-6/STAT3 pathway activation was evaluated through immunohistochemical staining and western blot. In the current study, silibinin significantly inhibited the viability of intestinal tumor cells. The production of inflammatory cytokines and the phosphorylation of STAT3 were both inhibited in intestinal tumor cells. Meanwhile, silibinin decreased the amount and size of tumors in AOM/DSS mice. Colitis and tumor scores were decreased accompanying with inhibition of colonic tumor cell proliferation and promotion of cellular apoptosis. Additionally, silibinin could reduce the production of inflammatory cytokines and attenuate the impairment of colonic mucosal barrier. Furthermore, STAT3 phosphorylation was significantly suppressed by silibinin. In conclusion, silibinin could protect against colitis-associated tumorigenesis in mice via inhibiting IL-6/STAT3, which showed promising chemopreventive potential of CAC.